Fly ash-based flame retardant, preparation method, polypropylene composite material and application

By using fly ash-based flame retardant in polypropylene, the compatibility and water resistance of polypropylene composite materials are solved by activating fly ash and covering the flame retardant components, and the flame retardant performance and mechanical properties are improved , avoid photooxidation and degradation, meet high temperature and wear resistance requirements.

CN119219987APending Publication Date: 2024-12-31CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410641412.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing expanded flame retardant has poor compatibility with polypropylene matrix, poor water resistance, and easy to be photooxidized and degraded, resulting in poor flame retardant and mechanical properties of polypropylene composite materials.

Method used

Using fly ash-based flame retardant, the core is formed by activating fly ash and covering the surface with a composite material containing phosphorus compounds, polyol organic compounds, triazine nitrogen-containing heterocyclic organic compounds and amino resin polymers. shell structure improves its compatibility and stability in polypropylene.

Benefits of technology

The flame retardant properties and mechanical properties of polypropylene composite materials are significantly improved, their water resistance and light resistance are enhanced, photooxidation and degradation are avoided, and the high temperature and wear resistance requirements of polypropylene products are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a fly ash-based flame retardant, a preparation method, a polypropylene composite material and application. The fly ash-based flame retardant comprises: an activated fly ash core made of activated fly ash, the surface of which has polarity; the flame-retardant coating layer is coated on the surface of the porous activated fly ash core body; the flame-retardant coating layer is made of a composite material comprising a phosphorus-containing compound, a polyol organic matter, a triazine nitrogen-containing heterocyclic organic compound and an amino resin polymer. The problems that in the prior art, a common intumescent flame retardant is poor in compatibility with a polypropylene matrix, or poor in precipitation resistance, or is prone to photooxidative degradation, and consequently the flame retardant property and the mechanical property of a polypropylene composite material are poor are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant composite materials, and in particular to a fly ash-based flame retardant and a preparation method thereof, and a polypropylene composite material and application thereof. Background Art

[0002] Based on the characteristics of high temperature resistance, corrosion resistance and good electrical insulation of polypropylene, and its low relative density, superior mechanical properties, low price and easy processing and molding, it is widely used in the fields of automobiles, electronic appliances, agricultural machinery, water conservancy, etc., and has become the fastest growing variety of general resins. However, since polypropylene itself is a flammable material, its oxygen index is only 17.4-18.5%, and its carbonization rate is low, it is easy to produce droplets during combustion, which leads to the spread of flames and fires, making many unsafe factors in the application process. In order to further expand the application scope of polypropylene materials, the research on flame retardant modification of polypropylene has always been a research hotspot. Improving the flame retardancy of polypropylene by adding intumescent flame retardants to polypropylene is currently the most commonly used approach. The intumescent flame retardant is mainly composed of gas source, carbon source and acid source, and releases non-combustible gas and water vapor during the combustion process to form an intumescent carbon layer to play a flame retardant role.

[0003] Chinese invention patent CN103333406 discloses a modified intumescent flame-retardant polypropylene composition and its preparation method. The polypropylene composition is a flame-retardant composite material prepared by polypropylene, toughening agent, compound intumescent flame retardant, nano zinc oxide, vinyl silane coupling agent, and polyethylene wax. The flame-retardant composite material has low tensile properties. Chinese invention patent CN103059407 discloses a polypropylene composite material, its preparation method and application. The polypropylene composite material is composed of polypropylene, toughening agent, white oil, flame retardant, anti-dripping agent, nucleating agent, dispersant and antioxidant, etc. The polypropylene composite material has both flame retardant and transparent properties. The flame retardant is a commercially available product based on non-fly ash, and the flame retardant component cannot be adjusted according to needs. Chinese invention patent CN103012852B discloses a microcapsule fly ash-based flame retardant, which has the organic phase and PN organic flame retardant characteristics of PN organic flame retardant, and has the common advantages of organic and inorganic flame retardants. It can be widely used in various types of organic rigid foam products, but the flame retardant performance has not been verified. Chinese patent CN114437459A discloses a composite material for double-walled corrugated pipes, using fly ash as a base material, preparing it into a flame retardant through modification, then adding a heat-resistant additive to the composite material to improve the heat resistance of the composite material, and finally preparing a polypropylene composite material suitable for double-walled corrugated pipes by overcoming the interaction between inorganic fillers and polymers. However, acetonitrile is used in the preparation process of the flame retardant, which is not environmentally friendly and healthy. In addition, after adding flame retardants in the prior art, the mechanical properties of the composite material deteriorate due to poor compatibility, which cannot meet the requirements of practical applications, thereby putting forward new requirements for the rigidity of polypropylene products. Usually, inorganic fillers such as glass fiber, calcium carbonate, and talcum powder are added to improve the rigidity of flame-retardant polypropylene to meet the performance and processing requirements of the product. However, glass fiber easily causes the carbon layer of the intumescent flame retardant to break, and calcium carbonate can reduce the flame retardant effect of the flame retardant to a certain extent.

[0004] In summary, the intumescent flame retardant in the prior art has the following defects: the flame retardant is highly hygroscopic, especially because the pentaerythritol component contained therein is easy to absorb moisture, resulting in poor water resistance of the flame retardant polymer; and the polarity of the intumescent flame retardant and the polymer is very different, resulting in poor compatibility; and the relative molecular mass of the substances in the flame retardant is small, and it is very easy to migrate to the surface of the polymer, making the appearance of the flame retardant product worse; and the intumescent flame retardant is sensitive to light and easily absorbs ultraviolet rays, thereby accelerating the photo-oxidative degradation rate of the polymer. The present invention provides a fly ash-based flame retardant and a preparation method, a polypropylene composite material and an application to improve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a fly ash-based flame retardant and a preparation method, a polypropylene composite material and an application, so as to solve the problem that the commonly used intumescent flame retardants in the prior art have poor compatibility with the polypropylene matrix, poor precipitation resistance, or are easily degraded by photooxidation, thereby resulting in poor flame retardancy and mechanical properties of the polypropylene composite material.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a fly ash-based flame retardant, which comprises: an activated fly ash core, whose material is activated fly ash, and the surface of the activated fly ash has polarity; a flame retardant coating layer, which is coated on the surface of the porous activated fly ash core; the material of the flame retardant coating layer is a composite material including phosphorus-containing compounds, polyol organic matter, triazine nitrogen-containing heterocyclic organic compounds and amino resin polymers.

[0007] Furthermore, the particle size D50 of the fly ash-based flame retardant is 15 to 1000 μm; preferably, the specific surface area of ​​the activated fly ash core is 300 to 600 m 2 / kg, the particle size D50 is 10-320 μm, and more preferably 15-45 μm; preferably, in the flame retardant coating layer, the weight ratio of the phosphorus-containing compound, the polyol organic matter, the triazine nitrogen-containing heterocyclic organic compound and the amino resin polymer is (2-8):(1-3):(1-3):1.

[0008] Further, the activated fly ash is fly ash obtained by alkalizing and acidifying the fly ash in sequence; preferably, the phosphorus-containing compound is selected from one or more of ammonium polyphosphate, phenyl dichloride phosphate or triphenyl phosphite; preferably, the polyol organic matter is selected from one or more of pentaerythritol, sorbitol or starch; preferably, the triazine nitrogen-containing heterocyclic organic compound is selected from one or more of melamine, polyphthalamide or dicyandiamide; preferably, the amino resin polymer is selected from one or more of melamine-formaldehyde resin polymer, melamine cyanurate or polyamide polyamine epichlorohydrin polymer; preferably, the degree of polymerization of the amino resin polymer is 3 to 20, and the weight average molecular weight Mw is 750 to 3500Da; preferably, the thickness of the flame retardant coating layer is 1 to 3μm; preferably, the composition of the fly ash is as follows, by weight percentage: 40 to 60wt% of SiO 2 , 17-30wt% Al 2 O 3 , 2~12wt%Fe 2 O 3 , 1-10wt% CaO, 0.5-2wt% MgO, 0.1-2wt% TiO 2 and 0.5-4wt% Na 2 O and 0.5-4wt% K 2O.

[0009] According to another aspect of the present invention, a method for preparing the above-mentioned fly ash-based flame retardant is also provided, which comprises: step S1, providing activated fly ash; step S2, coating a flame retardant coating layer on the surface of an activated fly ash core body formed by the activated fly ash to obtain a fly ash-based flame retardant.

[0010] Furthermore, the step of providing activated fly ash in step S1 includes: calcining the fly ash in an inorganic alkali solution to obtain an alkalized material; ultrasonically treating the alkalized material in an inorganic acid solution to acidify it, and then adding a surfactant to obtain activated fly ash; and / or, step S2 includes: dispersing the activated fly ash and a phosphorus-containing compound, a polyol organic matter, and a triazine nitrogen-containing heterocyclic organic compound in a solvent, and then adding an amino resin polymer prepolymer for heating treatment to polymerize the amino resin polymer prepolymer to obtain activated fly ash coated with a flame retardant coating layer, that is, a fly ash-based flame retardant.

[0011] Further, the inorganic base is selected from one or more of sodium hydroxide, sodium carbonate, potassium hydroxide or potassium carbonate; preferably, the inorganic acid is selected from one or more of hydrochloric acid, nitric acid or sulfuric acid, and further preferably, the concentration of the inorganic acid is 1-2.5 mol / L; preferably, the surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate or sodium methacrylate hydroxypropane sulfonate; preferably, by weight percentage, the weight ratio of the inorganic base, the inorganic acid and the surfactant to the fly ash is (0.1-0.3):(0.1-0.3):(1-3):1; preferably, by weight percentage, the prepolymer of the amino resin polymer is added in an amount of 1:1 of the fly ash. 0.1-1.0wt% of the flame retardant precursor; preferably, the solvent is selected from one or more of ethanol, diethylene glycol or ethylene glycol; preferably, the prepolymer of the amino resin polymer is selected from one or more of melamine-formaldehyde resin polymer, urea-formaldehyde resin polymer or phenolic resin polymer; preferably, in the preparation step of activated fly ash, after ultrasonic treatment and before adding the surfactant, it is also necessary to carry out water washing, and it is further preferred to wash with water until the pH value of the material after ultrasonic treatment is 6.5-7.5; preferably, the fly ash in step S1 is fly ash discharged from a coal-fired power plant or a coal chemical boiler, and before activation, the fly ash is also required to be calcined to remove residual carbon therein, as well as ground and screened.

[0012] Furthermore, in terms of weight percentage, the weight ratio of the total amount of phosphorus-containing compounds, polyol organic matter and triazine nitrogen-containing heterocyclic organic compound added to the activated fly ash is (18-52):1; preferably, the calcination treatment temperature is 750-950°C, and the calcination time is 1-3h; preferably, the power of the ultrasonic treatment is 100-500W, and the ultrasonic time is 0.5-5h; preferably, the temperature of the heating treatment in step S2 is 60-90°C, and the treatment time is 2-8h; preferably, the temperature of the heating treatment in the preparation step of activated fly ash is 70-80°C, and the treatment time is 2.5-12h.

[0013] According to another aspect of the present invention, a polypropylene composite material is provided, which comprises the above-mentioned fly ash-based flame retardant, or the fly ash-based flame retardant obtained by the preparation method of the above-mentioned fly ash-based flame retardant.

[0014] Further, the polypropylene composite material includes polypropylene, a fly ash-based flame retardant, an antioxidant, a compatibilizer, an anti-ultraviolet aging agent, a light stabilizer and an auxiliary agent; preferably, the components of the polypropylene composite material are as follows, by weight: 45 to 70 parts of polypropylene, 25 to 46 parts of a fly ash-based flame retardant, 3 to 5 parts of a compatibilizer, 0.1 to 2.0 parts of an antioxidant, 0.05 to 0.50 parts of an anti-ultraviolet aging agent, 0.05 to 0.50 parts of a light stabilizer and 0.1 to 1.0 parts of an auxiliary agent; preferably , the polypropylene is homopolymer polypropylene and / or impact-resistant copolymer polypropylene; preferably, the antioxidant is selected from one or more of hindered phenol main antioxidants, phosphite antioxidants or dilauryl thiodipropionate; preferably, the compatibilizer is maleic anhydride grafted polypropylene and / or acrylic acid grafted polypropylene; preferably, the UV aging agent is UV531 and / or UV326; preferably, the light stabilizer is hindered amine stabilizer T770 and / or JC783; preferably, the auxiliary agent is one or more of calcium stearate, white oil or EBS.

[0015] According to another aspect of the present invention, there is provided an application of the polypropylene composite material in the fields of automobiles, electronic appliances, agricultural machinery and water conservancy.

[0016] The invention effectively solves the problem that the commonly used intumescent flame retardants in the prior art have poor compatibility with the polypropylene matrix, poor precipitation resistance, or are easily degraded by photooxidation, thereby resulting in poor flame retardancy and mechanical properties of the polypropylene composite material. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0018] According to the background technology of the present invention, the intumescent flame retardant commonly used in the prior art releases non-combustible gas and water vapor during combustion to form an intumescent carbon layer to improve the flame retardancy of polypropylene, which often has many problems. For example, because it contains pentaerythritol, the flame retardant has strong hygroscopicity and the water resistance of polypropylene is very poor; the polarity of the intumescent flame retardant and polypropylene is very different, resulting in poor compatibility and poor mechanical properties of polypropylene; and the relative molecular mass of the substance in the intumescent flame retardant is very small, which is very easy to migrate to the surface of the polymer and precipitate, and the intumescent flame retardant is sensitive to light, easily absorbs ultraviolet rays and accelerates the photo-oxidative degradation of the polymer, thereby greatly reducing the flame retardancy of polypropylene. In view of the above problems, the present invention provides a fly ash-based flame retardant, which includes: an activated fly ash core, whose material is activated fly ash, and the surface of the activated fly ash has polarity; a flame retardant coating layer, which is coated on the surface of the porous activated fly ash core; the material of the flame retardant coating layer is a composite material including phosphorus-containing compounds, polyol organic matter, triazine nitrogen-containing heterocyclic organic compounds and amino resin polymers.

[0019] Compared with the intumescent flame retardant in the prior art, which forms an intumescent carbon layer during the combustion process to play a flame retardant role, the present invention creatively uses fly ash as the matrix of the flame retardant, because fly ash, as a kind of inorganic metal micro-bead particles, has a large specific surface area and has strong rigidity itself, and also has good dispersibility, wear resistance and heat resistance, and its physical and chemical properties are stable. More importantly, it has the characteristics of self-extinguishing, smoke elimination and high temperature resistance in the flame retardant process applied to polymer materials. In particular, the fly ash used in the present invention is activated fly ash after activation treatment, and the polarity of its surface is polar and / or weak polarity. At the same time, it also benefits from its own microporous structure with a large specific surface area, thereby overcoming the problem of poor compatibility of conventional flame retardants in the subsequent application to polypropylene materials.

[0020] More importantly, the present invention adopts an in-situ polymerization method to coat the flame retardant components of the flame retardant coating layer on the activated fly ash, so that the flame retardant components can be evenly coated on the surface of the activated fly ash core, thereby obtaining a "core-shell" structure with fly ash as the core and the flame retardant coating layer coated on its outer surface. On the one hand, based on the flame retardant coating layer coated on the inner and outer surfaces of the pores of the fly ash core, the fly ash-based flame retardant is less likely to be exposed to light during the combustion process, thereby greatly slowing down its photo-oxidative degradation rate, thereby improving its flame retardant performance; on the other hand, based on the coating structure of the fly ash-based flame retardant, the flame retardant components in the flame retardant coating layer are coated on the outer surface of the rigid skeleton of the fly ash, thereby weakening the hygroscopicity of the fly ash-based flame retardant and improving its water resistance. In addition, compared with conventional flame retardant components (phosphorus-containing compounds, polyol organic substances, triazine nitrogen-containing heterocyclic organic compounds), the flame retardant components in the present invention also have additional resin polymers added thereto. Adding them to the flame retardant coating layer can further improve the precipitation resistance and stability of the fly ash-based flame retardant, thereby enabling it to have excellent flame retardant properties and mechanical properties when subsequently applied to polypropylene materials.

[0021] In order to further improve the flame retardant properties of the fly ash-based flame retardant, the particle size D50 of the fly ash-based flame retardant is preferably 15 to 1000 μm. In order to further improve the water resistance and precipitation resistance of the fly ash-based flame retardant, the specific surface area of ​​the activated fly ash core is preferably 300 to 600 m 2 / kg, the particle size D50 is 10-320μm, and more preferably 15-45μm; in the flame retardant coating layer, the weight ratio of the phosphorus-containing compound, the polyol organic matter, the triazine nitrogen-containing heterocyclic organic compound and the amino resin polymer is (2-8):(1-3):(1-3):1, thereby further improving the flame retardant properties of the fly ash-based flame retardant.

[0022] In a preferred embodiment, the activated fly ash is fly ash obtained by alkalizing and acidifying the fly ash in sequence, thereby further improving the polarity of the fly ash surface, converting it from non-polar to polar, thereby improving its polar compatibility when it is subsequently applied to polypropylene materials. In order to further improve the flame retardant properties of the fly ash-based flame retardant, the phosphorus-containing compound is preferably selected from one or more of ammonium polyphosphate, dichlorophenyl phosphate or triphenyl phosphite; the polyol organic matter is selected from one or more of pentaerythritol, sorbitol or starch; the triazine nitrogen-containing heterocyclic organic compound is selected from one or more of melamine, polyphthalamide or dicyandiamide; the amino resin polymer is selected from one or more of melamine-formaldehyde resin polymer, melamine cyanurate or polyamide polyamine epichlorohydrin polymer; further preferably, the degree of polymerization of the amino resin polymer is 3 to 20, and the weight average molecular weight Mw is 750 to 3500Da; the thickness of the flame retardant coating is preferably 1 to 3 μm, so that the structure of the fly ash-based flame retardant is more stable.

[0023] Preferably, the fly ash has the following composition by weight percentage: 40-60wt% SiO 2 , 17-30wt% Al 2 O 3 , 2~12wt%Fe 2 O 3 , 1-10wt% CaO, 0.5-2wt% MgO, 0.1-2wt% TiO 2 and 0.5-4wt% Na 2 O and K 2 O.

[0024] Another aspect of the present invention provides a method for preparing a fly ash-based flame retardant, the preparation method comprising: step S1, providing activated fly ash; step S2, coating a flame retardant coating layer on the outer surface of an activated fly ash core body formed by the activated fly ash core body to obtain a fly ash-based flame retardant.

[0025] Those skilled in the art can first take activated fly ash, and then coat the outer surface of the activated fly ash core with a flame retardant coating layer to obtain the above-mentioned fly ash-based flame retardant. The fly ash-based flame retardant obtained by the preparation method of the present invention has excellent water resistance, precipitation resistance, excellent compatibility with the polymer matrix, and the characteristics of avoiding photooxidative decomposition. The preparation method of the present invention is simple to operate, suitable for industrialization, and has broad prospects for industrial application.

[0026] In a preferred embodiment, the preparation method of the above-mentioned fly ash-based flame retardant: step S1 includes: providing activated fly ash; calcining the fly ash in an inorganic alkali solution to obtain an alkalized material, ultrasonically treating the alkalized material in an inorganic acid solution to acidify it, and then adding a surfactant to obtain activated fly ash; and / or step S2 includes: dispersing the activated fly ash and a phosphorus-containing compound, a polyol organic matter, and a triazine nitrogen-containing heterocyclic organic compound in a solvent, and then adding an amino resin polymer prepolymer for heating treatment to polymerize the amino resin polymer prepolymer to obtain activated fly ash coated with a flame retardant coating layer, that is, a fly ash-based flame retardant.

[0027] A person skilled in the art may first calcine fly ash in an inorganic alkali solution to obtain an alkalized material, subject the alkalized material to ultrasonic treatment in an inorganic acid solution to acidification, and then add a surfactant to obtain activated fly ash; then, after dispersing the activated fly ash with a phosphorus-containing compound, a polyol organic matter, and a triazine nitrogen-containing heterocyclic organic compound in a solvent, add an amino resin polymer prepolymer and heat-treat the prepolymer to polymerize the amino resin polymer prepolymer, and obtain activated fly ash coated with a flame-retardant coating layer, i.e., a fly ash-based flame retardant, by in-situ polymerization.

[0028] In a preferred embodiment, the fly ash is fly ash discharged from coal-fired power plants or coal chemical boilers, and the fly ash needs to be ground and sieved before activation to obtain a fly ash-based flame retardant with better performance. The fly ash-based flame retardant has excellent water resistance, precipitation resistance, excellent compatibility with polymer matrix, and avoids photooxidative decomposition.

[0029] In order to further promote the full activation of fly ash, better change the surface polarity of fly ash and improve its compatibility with the polymer matrix, the inorganic base is preferably selected from one or more of sodium hydroxide, sodium carbonate or potassium carbonate; the inorganic acid is selected from one or more of hydrochloric acid, nitric acid or sulfuric acid, and the concentration of the inorganic acid is further preferably 1-2.5 mol / L; the surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate or sodium methacrylate hydroxypropane sulfonate; further preferably, in terms of weight percentage, the weight ratio of the inorganic base, inorganic acid and surfactant to the fly ash is (0.1-0.3): (0. 1~0.3):(1~3): 1; In order to further improve the water resistance and precipitation resistance of the fly ash-based flame retardant, the prepolymer of the amino resin polymer is preferably added in an amount of 0.1~1.0wt% of the fly ash-based flame retardant precursor by weight percentage; the solvent is preferably selected from one or more of ethanol, diethylene glycol or ethylene glycol, so that the flame retardant has better solubility in the solvent. In the preparation step of activated fly ash, after ultrasonic treatment and before adding the surfactant, a water washing operation is required to remove impurities on the surface of the activated fly ash, thereby improving the polarity of the fly ash-based flame retardant. It is further preferred that the pH value of the material after water washing is 8~10 after ultrasonic treatment.

[0030] In a preferred embodiment, the weight ratio of the total amount of phosphorus-containing compounds, polyol organic matter and triazine nitrogen-containing heterocyclic organic compound added to the activated fly ash is (18-52):1, thereby further improving the flame retardant properties of the fly ash-based flame retardant; the calcination treatment temperature is preferably 750-950°C, and the calcination time is 1-3h, thereby further removing the residual carbon in the fly ash; the ultrasonic treatment power is preferably 100-500W, and the ultrasonic time is 0.5-5h, thereby further improving the complete activation of the fly ash; the heating treatment temperature in step S2 is preferably 60-90°C, and the treatment time is 2-8h, so as to improve the thermal stability of the fly ash-based flame retardant, so that the added amino resin polymer reacts more fully with other components, and improves the water resistance and precipitation resistance of the fly ash-based flame retardant. It is further preferred that the heating treatment temperature in the preparation step of activated fly ash is 70-80°C, and the treatment time is 2.5-12h.

[0031] Another aspect of the present invention provides a polypropylene composite material, which comprises the above-mentioned fly ash-based flame retardant, or the fly ash-based flame retardant obtained by the above-mentioned preparation method of the fly ash-based flame retardant. The polypropylene composite material has excellent flame retardant properties and mechanical stability.

[0032] In a preferred embodiment, the polypropylene composite material comprises polypropylene, the fly ash-based flame retardant, an antioxidant, a compatibilizer, an anti-ultraviolet aging agent, a light stabilizer and an auxiliary agent; in parts by weight, the preferred components of the polypropylene composite material are as follows: 45 to 70 parts of polypropylene, 25 to 46 parts of fly ash-based flame retardant, 3 to 5 parts of a compatibilizer, 0.1 to 2.0 parts of an antioxidant, 0.05 to 0.50 parts of an anti-ultraviolet aging agent, 0.05 to 0.50 parts of a light stabilizer and 0.1 to 1.0 parts of an auxiliary agent;

[0033] In order to further improve the flame retardant properties and mechanical stability of the polypropylene composite material, the polypropylene is preferably homopolypropylene and / or impact copolymer polypropylene; further preferably, the melt flow rate of the homopolypropylene (at 230°C and 2.16Kg) is 10-65g / 10min, and the melt flow rate of the impact copolymer polypropylene (at 230°C and 2.16Kg) is 2-50g / 10min. More preferably, when a combination of homopolypropylene and impact polypropylene is selected, the difference in melt flow rates between the two is 10-20g / 10min, and the weight ratio of homopolypropylene to impact polypropylene is (2-4):1.

[0034] In a preferred embodiment, in order to further improve the flame retardancy and mechanical stability of the polypropylene composite material, the antioxidant is preferably selected from one or more of a hindered phenolic primary antioxidant, a phosphite antioxidant or dilauryl thiodipropionate; wherein the hindered phenolic primary antioxidant is antioxidant 1010 and / or antioxidant 1076, and the phosphite secondary antioxidant is selected from one or more of antioxidant 168, antioxidant 618, antioxidant 215, antioxidant 245 or antioxidant 626. The weight ratio of the hindered phenolic primary antioxidant to the phosphite secondary antioxidant is (0.3-1):1. The weight ratio of the hindered phenolic main antioxidant to dilauryl thiodipropionate is (1-3):1, the preferred compatibilizer is maleic anhydride grafted polypropylene and / or acrylic acid grafted polypropylene; the UV aging agent is UV531 and / or UV326; the preferred light stabilizer is hindered amine stabilizer T770 and / or JC783; the preferred auxiliary agent is one or more of calcium stearate, white oil or EBS, so as to improve the comprehensive performance of the polypropylene composite material.

[0035] Another aspect of the present invention provides an application of a polypropylene composite material in the fields of automobiles, electronic appliances, agricultural machinery and water conservancy.

[0036] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0037] Example 1

[0038] Fly ash is the fly ash discharged from coal-fired power plants. Calculated by weight percentage, the composition of the fly ash is as follows: 50wt% SiO 2 , 20wt%Al 2 O 3 , 10wt%Fe 2 O 3 , 10wt% CaO, 2wt% MgO, 2wt% TiO 2 and 4wt% Na 2 O and 2wt% K 2 O.

[0039] Step S1, calcining the fly ash at 800°C for 6 hours to remove the residual carbon, then grinding and sieving after cooling to obtain particles with a particle size D50 of 15 μm. 2 CO 3 The solution was fully ground and calcined at 850°C for 3h. After cooling, 1000mL of 1.15mol / L hydrochloric acid was added, stirred at room temperature for 4h, ultrasonically treated for 3h, cooled to room temperature, and then rinsed with distilled water until neutral (pH value was 7.5). Then 4.3g of sodium dodecyl sulfate surfactant was added, the temperature was raised to 80°C, stirred for 3 hours, filtered and dried under hot air conditions at 100°C to obtain activated fly ash. The specific surface area of ​​the activated fly ash is 450m 2 / g, particle size D50 is 16.5μm, Na + The surface has a large positive charge and a small spherical spatial structure, which aggregates into a semi-micelle structure and hinders particle agglomeration.

[0040] Step S2, take the above-mentioned activated fly ash and 60g of ammonium polyphosphate, 20g of pentaerythritol, 20g of melamine in 40mL of anhydrous ethanol solvent and mix them, and stir for 40min. Wherein, the weight ratio of adding ammonium polyphosphate, pentaerythritol, melamine and activated fly ash is 12:1, and then 50mL of melamine-formaldehyde polycondensate is added, and its polymerization degree is 10, and the weight average molecular weight is 2500Da, and after stirring evenly, it is kept at 100°C for 1h, and after low temperature drying and grinding, a fly ash-based flame retardant is obtained. The particle size D50 of the fly ash-based flame retardant is 18μm, wherein, in the flame retardant coating layer, the weight ratio of ammonium polyphosphate, pentaerythritol, melamine and melamine-formaldehyde polycondensate is 4.5:1.5:1.5:1. Wherein, the thickness of the coating layer is 3μm.

[0041] The preparation method of melamine-formaldehyde polycondensate is as follows: in a three-necked flask equipped with a stirrer, a reflux condenser and a thermometer, 75 g of formaldehyde solution (40 wt%), 8 g of methanol and 24 g of triethanolamine are added and mixed, and then heated to 85° C. and maintained for 3 h; then 20 g of melamine is added, and the temperature is raised to 90° C. and maintained for 6 h to obtain melamine-formaldehyde polycondensate; finally, 50 mL of distilled water is added to form a stable melamine-formaldehyde resin prepolymer.

[0042] Take 550g of the fly ash-based flame retardant prepared above and homopolymer polypropylene (PP is 1100N, melt flow rate 12g / 10min), 50g of compatibilizer maleic anhydride grafted polypropylene (KT-1), 6.7g of hindered phenol antioxidant 1010, 3.3g of antioxidant 168 and antioxidant 1010 (the ratio of the two is 2:1), 5g of UV aging agent UV531, 5g of hindered amine stabilizer T770 and 10g of calcium stearate auxiliary agent, and mix the above raw materials at high speed for 1min. After the mixture is metered by the main feeder, it enters the co-rotating twin-screw extruder for melt plasticization, and after extrusion, it is water-cooled and granulated. The temperatures of each zone of the extruder screw are 175℃, 190℃, 200℃, 210℃, 230℃, 210℃, 200℃, and the screw speed is controlled at 200rpm to obtain the above polypropylene composite material.

[0043] The components of the polypropylene composite material are as follows by weight: 55 parts of polypropylene, 40 parts of fly ash-based flame retardant, 5 parts of compatibilizer, 0.1 parts of antioxidant, 0.05 parts of UV aging agent UV531, 0.05 parts of hindered amine stabilizer T770, and 0.1 parts of calcium stearate.

[0044] Example 2

[0045] The only difference from Example 1 is:

[0046] Step S1, calcining the fly ash at 800°C for 6 hours to remove the residual carbon, then grinding and sieving after cooling to obtain particles with a particle size D50 of 33 μm. 2 CO 3 The solution was fully ground and calcined at 900°C for 3h. After cooling, 750mL of 30wt% hydrochloric acid was added, stirred at room temperature for 4h, ultrasonically treated for 3h, cooled to room temperature, and then rinsed with distilled water until neutral (pH value was 7.5). Then 3.2g of sodium dodecyl sulfate surfactant was added, the temperature was raised to 75°C, stirred for 2 hours, filtered and dried under hot air conditions at 100°C to increase the surface polarity to obtain activated fly ash. The specific surface area of ​​the activated fly ash is 325m 2 / g, and the particle size D50 is 84μm.

[0047] 5 g of white oil, antioxidant 1010 and antioxidant DLTP (the ratio of the two is 2:1) are additionally added to the polypropylene composite material. The components in the polypropylene composite material are as follows, by weight: 50 parts of polypropylene, 45 parts of fly ash-based flame retardant, 5 parts of compatibilizer, 0.1 part of antioxidant, 0.05 parts of UV aging agent UV531, 0.05 parts of hindered amine stabilizer T770, 0.1 parts of calcium stearate, and 0.05% of white oil.

[0048] Example 3

[0049] The difference from Example 2 is that 100 g of impact copolymer polypropylene (2500H, melt flow rate 2.5 g / 10 min) is added to the polypropylene composite material. The components of the polypropylene composite material are as follows by weight: 50 parts of polypropylene, 45 parts of fly ash-based flame retardant, 5 parts of compatibilizer, 0.1 parts of antioxidant, 0.05 parts of UV aging agent UV531, 0.05 parts of hindered amine stabilizer T770, 0.1 parts of calcium stearate, and 0.05 parts of white oil.

[0050] Example 4

[0051] The only difference from Example 1 is that in the polypropylene composite material, the polypropylene is homopolymer polypropylene and impact-resistant copolymer polypropylene (the ratio of the two is 2:1). In terms of weight parts, the components in the polypropylene composite material are as follows: 50 parts of polypropylene, 45 parts of fly ash-based flame retardant, 5 parts of compatibilizer, 0.1 parts of antioxidant, 0.05 parts of UV aging agent UV531, 0.05 parts of hindered amine stabilizer T770, 0.1 parts of calcium stearate, and 0.05 parts of white oil.

[0052] Example 5

[0053] The only difference from Example 1 is that: Step S2, take the above-mentioned activated fly ash and 60g of ammonium polyphosphate, 30g of sorbitol, and 20g of melamine in 40mL of anhydrous ethanol solvent and mix them, and stir for 40min. Wherein, the weight ratio of the total weight of ammonium polyphosphate, pentaerythritol, and melamine to the activated fly ash is 12.75:1, and then add 50mL of melamine-formaldehyde condensation product, whose degree of polymerization is 10 and weight-average molecular weight is 2500Da, stir evenly, keep at 100°C for 1h, dry at low temperature and grind to obtain a fly ash-based flame retardant. The particle size D50 of the fly ash-based flame retardant is 18μm, wherein, in the flame retardant coating layer, the weight ratio of ammonium polyphosphate, sorbitol, melamine and melamine-formaldehyde condensation product is 6:3:2:1. Wherein, the thickness of the coating layer is 3μm.

[0054] Comparative Example 1

[0055] The only difference from Example 1 is that an intumescent flame retardant prepared by combining ammonium polyphosphate, pentaerythritol and melamine (mass ratio of 3:1:1) is used to replace the fly ash-based flame retardant.

[0056] Comparative Example 2

[0057] The only difference from Example 2 is that an intumescent flame retardant prepared by combining ammonium polyphosphate, pentaerythritol and melamine (mass ratio of 3:1:1) is used to replace the fly ash-based flame retardant.

[0058] Comparative Example 3

[0059] The only difference from Example 3 is that an intumescent flame retardant prepared by combining ammonium polyphosphate, pentaerythritol and melamine (mass ratio of 3:1:1) is used to replace the fly ash-based flame retardant.

[0060] Comparative Example 4

[0061] The only difference from Example 1 is that fly ash is directly mixed with ammonium polyphosphate, pentaerythritol and melamine (mass ratio 7:2.5:2.5:1) to obtain a fly ash-based flame retardant without a coating structure, replacing the coated fly ash-based flame retardant.

[0062] Comparative Example 5

[0063] The only difference from Example 1 is that: S1: the fly ash in the flame retardant is not activated. The proportion and method of the following experiments remain unchanged.

[0064] Comparative Example 6

[0065] The only difference from Example 1 is that the fly ash is calcined at 800° C. for 6 hours to remove the residual carbon therein, then ground and sieved after cooling, and particles with a particle size D50 of 104 μm are selected.

[0066] Performance Test:

[0067] (1) Mechanical properties

[0068] Mechanical properties tests include: tensile properties (tensile strength, tensile elongation at break), flexural properties (flexural strength, flexural modulus) and simply supported beam / cantilever beam notched impact strength tests.

[0069] ① According to the national standard for injection molded polypropylene specimens, tensile test specimens, bending test specimens and impact test specimens were prepared on the injection molding machine, and then the state was adjusted under constant temperature (temperature, 23°C) and constant humidity (humidity, 50%) conditions according to the national standard.

[0070] ② According to the national standards for tensile and bending tests, the tensile and bending test specimens were respectively subjected to tensile and bending tests on a universal material testing machine. The tensile strength test speed was 50mm / min and 5mm / min, and the bending modulus test speed was 2mm / min. The specimens with milled notches and state adjustment were tested for simply supported beam / cantilever beam notch impact strength on an impact testing machine.

[0071] (2) Flame retardant properties

[0072] A horizontal vertical combustion tester was used in accordance with the national standard GB / T 2408-2008 Method B. A sample with a size of 126 mm × 12.6 mm × 3.2 mm was fixed vertically on a rectangular frame under laboratory environmental conditions (23 ± 2 °C, 50 ± 5% RH). The sample was ignited with a specified flame in a combustion box, and the burning distance and time of the sample were measured to evaluate the vertical combustion level of the sample.

[0073] (3) Oxygen index

[0074] Use an oxygen index tester in accordance with the method specified in the national standard GB / T 2406.1-2008 & GB / T 2406.2-2009, take a sample with a size of 80mm×10mm×4mm, fix the sample vertically in a combustion tube under laboratory environmental conditions (23±2℃, 50±5%RH), fill it with a certain concentration of oxygen and nitrogen, ignite the top of the sample with an igniter, observe the combustion of the sample, and adjust the oxygen concentration accordingly until the limit oxygen concentration of the sample is measured to maintain balanced combustion, which is expressed as a percentage of oxygen content.

[0075] The results of the performance tests of the polypropylene composite materials prepared in the above examples and comparative examples are as follows:

[0076] Table 1

[0077]

[0078]

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fly ash-based flame retardant, characterized in that: The fly ash-based flame retardant comprises: The activated fly ash core is made of activated fly ash, and the surface of the activated fly ash has polarity; The flame retardant coating layer is coated on the surface of the porous activated fly ash core body; the material of the flame retardant coating layer is a composite material including phosphorus-containing compounds, polyol organic matter, triazine nitrogen-containing heterocyclic organic compounds and amino resin polymer.

2. The fly ash-based flame retardant according to claim 1, characterized in that: The particle size D50 of the fly ash-based flame retardant is 15 to 1000 μm; Preferably, the specific surface area of ​​the activated fly ash core is 300 to 600 m 2 / kg, particle size D50 is 10 to 320 μm, more preferably 15 to 45 μm; Preferably, in the flame retardant coating layer, the weight ratio of the phosphorus-containing compound, the polyol organic compound, the triazine nitrogen-containing heterocyclic organic compound and the amino resin polymer is (2-8): (1-3) in parts by weight: (1~3):1。 3. The fly ash-based flame retardant according to claim 1 or 2, characterized in that: The activated fly ash is fly ash obtained by sequentially subjecting fly ash to alkalization treatment and acidification treatment; Preferably, the phosphorus-containing compound is selected from one or more of ammonium polyphosphate, phenyl dichloride phosphate or triphenyl phosphite; Preferably, the polyol organic substance is selected from one or more of pentaerythritol, sorbitol or starch; Preferably, the triazine nitrogen-containing heterocyclic organic compound is selected from one or more of melamine, polyphthalamide or dicyandiamide; Preferably, the amino resin polymer is selected from one or more of melamine-formaldehyde resin polymer, melamine cyanurate or polyamide polyamine epichlorohydrin polymer; Preferably, the amino resin polymer has a degree of polymerization of 3 to 20 and a weight average molecular weight Mw of 750 to 3500 Da; Preferably, the thickness of the flame retardant coating is 1 to 3 μm; Preferably, the fly ash has the following components, measured by weight percentage: 40-60wt% SiO2, 17-30wt% Al2O3, 2-12wt% Fe2O3, 1-10wt% CaO, 0.5-2wt% MgO, 0.1-2wt% TiO2, 0.5-4wt% Na2O and 0.5-4wt% K2O.

4. A method for preparing a fly ash-based flame retardant according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, providing activated fly ash; Step S2, coating the surface of the activated fly ash core formed by the activated fly ash with a flame retardant coating layer to obtain the fly ash-based flame retardant.

5. The method for preparing a fly ash-based flame retardant according to claim 4, characterized in that: The step of providing the activated fly ash in step S1 comprises: calcining the fly ash in an inorganic alkali solution to obtain an alkalized material; ultrasonically treating the alkalized material in an inorganic acid solution to acidify it, and then adding a surfactant to obtain the activated fly ash; and / or The step S2 comprises: dispersing the activated fly ash, phosphorus-containing compounds, polyol organic matter, and triazine nitrogen-containing heterocyclic organic compounds in a solvent, and then adding an amino resin polymer prepolymer for heating treatment to polymerize the amino resin polymer prepolymer to obtain activated fly ash coated with a flame-retardant coating layer, i.e., the fly ash-based flame retardant.

6. The method for preparing a fly ash-based flame retardant according to claim 5, characterized in that: The inorganic base is selected from one or more of sodium hydroxide, sodium carbonate, potassium hydroxide or potassium carbonate; Preferably, the inorganic acid is selected from one or more of hydrochloric acid, nitric acid or sulfuric acid, and further preferably, the concentration of the inorganic acid is 1 to 2.5 mol / L; Preferably, the surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfonate or sodium methacrylate hydroxypropane sulfonate; Preferably, in terms of weight percentage, the weight ratio of the inorganic base, the inorganic acid and the surfactant to the fly ash is (0.1-0.3):(0.1-0.3):(1-3):1; Preferably, the prepolymer of the amino resin polymer is added in an amount of 0.1 to 1.0 wt % of the fly ash-based flame retardant precursor by weight percentage; Preferably, the solvent is selected from one or more of ethanol, diethylene glycol or ethylene glycol; Preferably, the amino resin polymer prepolymer is selected from one or more of a melamine-formaldehyde resin polymer, a urea-formaldehyde resin polymer or a phenol-formaldehyde resin polymer pair; Preferably, in the preparation step of the activated fly ash, after the ultrasonic treatment and before the addition of the surfactant, a water washing operation is required, and it is further preferred that the water washing is performed until the pH value of the material after the ultrasonic treatment is 6.5 to 7.5; Preferably, the fly ash in step S1 is fly ash discharged from coal-fired power plants or coal chemical boilers. Before the activation, the fly ash needs to be calcined to remove residual carbon therein, and ground and screened.

7. The method for preparing the fly ash-based flame retardant according to claim 5, characterized in that: In terms of weight percentage, the weight ratio of the total amount of the phosphorus-containing compound, the polyol organic compound and the triazine nitrogen-containing heterocyclic organic compound added to the activated fly ash is (18-52):1; Preferably, the calcination treatment temperature is 750-950°C, and the calcination time is 1-3h; Preferably, the power of the ultrasonic treatment is 100-500W, and the ultrasonic time is 0.5-5h; Preferably, the temperature of the heating treatment in step S2 is 60-90° C., and the treatment time is 2-8 hours; Preferably, the temperature of the heating treatment in the preparation step of the activated fly ash is 70-80° C., and the treatment time is 2.5-12 hours.

8. A polypropylene composite material, characterized in that: The polypropylene composite material comprises the fly ash-based flame retardant according to any one of claims 1 to 3, or the fly ash-based flame retardant obtained by the preparation method of the fly ash-based flame retardant according to any one of claims 4 to 7.

9. The polypropylene composite material according to claim 8, characterized in that: The polypropylene composite material comprises polypropylene, the fly ash-based flame retardant, an antioxidant, a compatibilizer, an anti-ultraviolet aging agent, a light stabilizer and an auxiliary agent; Preferably, the components of the polypropylene composite material are as follows, measured by weight: 45 to 70 parts of the polypropylene, 25 to 46 parts of the fly ash-based flame retardant, 3 to 5 parts of the compatibilizer, 0.1 to 2.0 parts of the antioxidant, 0.05 to 0.50 parts of the anti-ultraviolet aging agent, 0.05 to 0.50 parts of the light stabilizer, and 0.1 to 1.0 parts of the auxiliary agent; Preferably, the polypropylene is homopolymer polypropylene and / or impact copolymer polypropylene; Preferably, the antioxidant is selected from one or more of hindered phenolic primary antioxidants, phosphite antioxidants or dilauryl thiodipropionate; Preferably, the compatibilizer is maleic anhydride grafted polypropylene and / or acrylic acid grafted polypropylene; Preferably, the anti-ultraviolet aging agent is UV531 and / or UV326; Preferably, the light stabilizer is hindered amine stabilizer T770 and / or JC783; Preferably, the auxiliary agent is one or more of calcium stearate, white oil or EBS.

10. Use of the polypropylene composite material according to claim 8 or 9 in the fields of automobiles, electronic appliances, agricultural machinery and water conservancy.

Citation Information

Cited By

  • Polyethylene composite coiled material and preparation method thereof

    CN121136242A